Bagian Bapak Sepertiga dalam KHI Pasal 177 Merupakan Konsekwensi dari Bagian Ibu Thuluth al-Bâq; Analisis Ijtihad ‘Umar Bin Khat?t?âb - Syuhada' Syuhada' (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2016)
Instructions Qur’an about inheritance was so standard and tawqîfiyat. But there is still very limited and in the form of global instructions. The designation rules in global situation give open space to make ijtihâd. In the case of the mother part being with father and one of husband or wife has never happened in the past Apostles led to ‘Umar bin Khat?t?âb as caliph must make ijtihâd to give answers to completion. With this decision the mother part can be solved by maintaining the scale of two proportionate one for men and women by directing the understanding that the third part of mother on the condition it is third the rest of the treasure, not a third of the entire inheritance. However, when position of the father is not there, while his grandfather still exist and replace father in inheritance mother still get a piece a third of the inheritance because his grandfather is not equal to mother in inheritance. Part mother third of remainder having taken part husband in the case of above is to give the rule of law and consequences on the part of father become third though referred to inherit the remainder.